Wall heat transfer of unsteady near-wall flow in internal combustion engines. (September 2019) - Harada, Yuji; Uchida, Kenji; Tanaka, Tatsuya; Sato, Kiyotaka; Zhu, Qianjin; Fujimoto, Hidefumi; Yamashita, Hiroyuki; Tanahashi, Mamoru
Although the near-wall turbulence is not fully developed in the engine combustion chamber, wall heat transfer models based on flow characteristics in fully developed near-wall turbulence are typically employed in engine simulations to predict heat transfer. Only few studies reported the wall heat transfer mechanism in near-wall flow where the near-wall turbulence was not fully developed as expected in the engine combustion chamber. In this study, the velocity distribution and wall heat flux in such a near-wall flow were evaluated using a rapid compression and expansion machine. In addition to the experimental approach, a numerical simulation with highly resolved calculation mesh was applied in various flow fields expected in the engine combustion chamber. As a result, the turbulent Reynolds number that represents the relationship between turbulent production and dissipation varied in the wall boundary layer according to the near-wall flow condition. This behavior affects the wall heat transfer. Considering this finding, a new model was formulated by introducing a ratio of turbulent Reynolds number in an intended near-wall flow to that in fully developed near-wall turbulence. It was confirmed that the proposed model could improve the prediction accuracy of wall heat flux even in near-wall flow where the near-wall turbulence was not fully developed. By applying the proposed model in engine computational fluid dynamics, it was found that the proposed model could predict the wall heat flux in a homogeneous charge compression ignition gasoline engine with acceptable accuracy.